2001
DOI: 10.1523/jneurosci.21-13-04891.2001
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor Increases in the Uninjured Dorsal Root Ganglion Neurons in Selective Spinal Nerve Ligation Model

Abstract: Nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF) are two major members of the neurotrophin family. Using immunohistochemistry and in situ hybridization histochemistry, we examined the effect of L5 spinal nerve ligation (SPNL), a neuropathic pain model, on the expression of BDNF in the uninjured L4 dorsal root ganglion (DRG). After L5 SPNL, both immunoreactivity for BDNF and the hybridization intensity for BDNF mRNA increased mainly in the small- and medium-sized neurons. The percentage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
165
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 289 publications
(175 citation statements)
references
References 37 publications
8
165
0
2
Order By: Relevance
“…Furthermore, NGF and NT3 activate BK channels in rodent brain [36]. Axotomy from SNL may deprive L5 neurons of trophic support necessary to maintain I K(Ca) , whereas elevated NGF found in L4 DRGs after SNL [19] may promote greater than normal expression of I K(Ca) , as observed in this study.…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, NGF and NT3 activate BK channels in rodent brain [36]. Axotomy from SNL may deprive L5 neurons of trophic support necessary to maintain I K(Ca) , whereas elevated NGF found in L4 DRGs after SNL [19] may promote greater than normal expression of I K(Ca) , as observed in this study.…”
Section: Discussionsupporting
confidence: 58%
“…Male Sprague-Dawley rats, weighing 200-350 g, were used in all experiments. The spinal nerve ligation injury was performed under isoflurane anesthesia according to the method described by Fukuoka et al [21]. The skin was incised over the caudal lumber region and muscles were retracted.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported that intrathecal injection of trkB-IgG and anti-BDNF prevented the development of thermal hyperalgesia in the peripheral inflammation and neuropathic pain models Fukuoka et al, 2001;Groth and Aanonsen, 2002), although the action of BDNF in the dorsal horn is likely to be complex (Pezet et al, 2002;Malcangio and Lessmann, 2003). In contrast, TRPV1, one of the transducer proteins, can generate depolarizing currents in response to noxious thermal stimuli.…”
Section: Bdnf and Trpv1 Expression In Adjacent Intact L4 Drg Neurons mentioning
confidence: 99%